Pengaruh Faktor Personal, Faktor Organisasional Dan Faktor Non Organisasi Terhadap Komitmen Organisasional ( Studi Pada Pegawai Bagian Produksi PT. Kubota Indonesia ) - Sari, Fransisca Fitri Kurnia; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
To build togetherness in a relationship by activatingcommunication network in coordination to reach a goal in an organization issomething that needs to be socialized to all members. It must be carried outbecause the members involvement in work implementation has responsibility forthe success of members. Commitment is a circumstance of employees thatgenerates strong positive behavior to work organization. The purpose of thisresearch was to find out and analyze the influence of personal factor,organizational factor and non organization factor to organizational commitment atPT Kubota Indonesia. The population in this research was all employees of PTKubota Indonesia Semarang as 72 employees. The samples were 72 employees.The sampling technique used in this research was purposive sampling. The analysistool used in this research was multiple linier regression which was firstly examinedby validity and reliability test. The result showed that there was positive influenceof personal factor, organizational factor and non organization factor both partialand simultaneous. It means if personal factor, organizational factor and nonorganization factor improve, the organizational commitment will improve.Keywords : personal factor, organizational factor and non organization factor toorganizational commitment